Nourishing the Body, Disenfranchising the Spirit: Convivial Hospitality, Dignity, and Commensality in a Presbyterian Church in Toronto - Davidson, Lisa (Anthropologica, 2022)
Within the multicultural and multiracial city of Toronto Ontario, the space of the church is a place for racialized and white Presbyterian women to negotiate convivial hospitality, dignity, and notions of the good life. I use the concept of convivial hospitality to show how conviviality aligns with Christian hospitality when it centres on people’s will for spiritual and physical wellbeing through their relationships and interactions with others. This article focuses on the affective labour involved in the preparation of church community dinners, which were developed and organized by older, racialized Presbyterian women. Meal-time preparations are moments when convivial hospitality emerges among racialized women who pass the time by sharing their food, memories, and life stories, thus affirming a sense of dignity and belonging. Conviviality, however, takes an inhospitable turn when racialized women are subjected to undignified sociality. In exploring times when white Presbyterian women assisted with the community meals, the manner of their help coopted and disenfranchised racialized women from their service to the church and to God. What emerges is convivial inhospitality as racialized churchgoers are subjected to hierarchal interactions, making them feel like outsiders within their own church; yet, in caring for the wellbeing of white congregants to maintain social harmony and congregational unity, they tolerate the status quo which they see as Christian convivial hospitality.